2020
DOI: 10.2147/ott.s286600
|View full text |Cite
|
Sign up to set email alerts
|

<p>PD-1/PD-L1 Inhibitor Combined with Chemotherapy Can Improve the Survival of Non-Small Cell Lung Cancer Patients with Brain Metastases</p>

Abstract: Introduction Immune checkpoint inhibitor (ICI) monotherapy has limited efficacy in patients with non-small cell lung cancer (NSCLC) and brain metastases (BMs). With the wide use of ICI-based combinations, the efficacy of different ICI combination strategies in patients with NSCLC and BMs needs to be further elucidated. Methods We retrospectively reviewed 526 patients with non-small cell lung cancer (NSCLC) treated with ICIs from January 2016 to December 2019 in the Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The difference in the results might because of the inclusion of more studies and varying sample sizes. In a retrospective study [ 44 ], 77 patients with NSCLC with BM who received either immune combination chemotherapy or monotherapy were included. The results of subgroup analysis revealed that chemotherapy combined with ICIs led to a significantly superior OS rate compared with ICIs alone.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the results might because of the inclusion of more studies and varying sample sizes. In a retrospective study [ 44 ], 77 patients with NSCLC with BM who received either immune combination chemotherapy or monotherapy were included. The results of subgroup analysis revealed that chemotherapy combined with ICIs led to a significantly superior OS rate compared with ICIs alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, most active or untreated BM patients have been excluded from clinical trials. The intracranial response has not been determined in less‐selected patients with BM 20,47,48 . Additionally, a meta‐analysis by Yang et al 49 found that patients with BM who underwent ICIs combined with chemotherapy only experienced superior OS, but not PFS or iPFS than chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The intracranial response has not been determined in less‐selected patients with BM. 20 , 47 , 48 Additionally, a meta‐analysis by Yang et al 49 found that patients with BM who underwent ICIs combined with chemotherapy only experienced superior OS, but not PFS or iPFS than chemotherapy. Sun et al 47 suggested that ICIs combined with chemotherapy significantly showed superior survival (iPFS, PFS, and OS) than ICI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, immunotherapy for BM from NSCLC is being developed with other combination therapies, such as radiotherapy or chemotherapy (92)(93)(94)(95). Recent research has discovered that cancer patients having radiotherapy and/or chemotherapy have varied immunogenicity patterns, which could improve the function of immunotherapy, promote efficiency, and reduce side effects (96)(97)(98). Because of their potential to influence innate and adaptive immunity, certain chemotherapeutic drugs, such as cyclophosphamide, may improve the anticancer efficacy of immunotherapy.…”
Section: Recent Advancements In the Treatment Of Bm From Nsclc With I...mentioning
confidence: 99%